(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This study examines the impact of gamification on learning motivation and academic achievement among students. Gamification, the incorporation of game elements into non-game contexts, has emerged as a promising educational approach, hypothesized to enhance student engagement and learning outcomes. Drawing on a mixed-methods research design, this investigation involved a quantitative survey of 250 students and qualitative interviews with 15 educators, across various educational settings. The quantitative analysis utilized standardized measures of academic motivation and achievement, while qualitative data provided insights into the practical application and perceived effectiveness of gamification strategies. The findings indicate a significant positive correlation between the use of gamification in education and increased levels of student motivation. Specifically, elements such as points, leaderboards, and badges were identified as strong motivators, contributing to a more engaging learning environment. Furthermore, a moderate positive effect on academic achievement was observed, suggesting that while gamification significantly boosts motivation, its impact on achievement is conditional on factors like the design of the gamified system and the individual learner’s characteristics. The study contributes to the growing body of literature supporting gamification in educational contexts. It highlights the importance of strategic gamification design, tailored to educational content and learner profiles, to maximize its benefits. This research underscores the potential of gamification as a powerful tool in modern educational practices, capable of fostering not only greater motivation but also enhancing learning outcomes.